Effect of glaze cooling rate on mechanical properties of conventional and pressed porcelain on zirconia - Longhini, Diogo [UNESP]; Rocha, Cibele Oliveira de Melo [UNESP]; Medeiros, Igor Studart; Fonseca, Renata Garcia [UNESP]; Adabo, Gelson Luis [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to characterize a conventional and a pressed porcelain for zirconia core as to biaxial flexural strength (BFS), apparent fracture toughness (FT) and microstructure composition, and to investigate the effect of glaze cooling rate on the BFS of the zirconia/porcelain bilayers. Monolayers of conventional porcelain Vita VM9 and pressed porcelain Vita PM9 (n=15) (12 mm diameter x 1.2 mm thick) were prepared for the BFS test (MPa). Apparent fracture toughness (MPa.m1/2) was measured by indentation technique (n=15). t-Student test was performed for statistical analysis. Scanning electron microscopy and x-ray diffraction were used to analyze the porcelain’s microstructure. For the BFS of bilayers, zirconia discs (12 mm diameter x 1 mm thick) (Vita In-Ceram YZ) were veneered with the two porcelains (1 mm thick). After the glaze firing simulation, the specimens were submitted to fast or slow cooling (n=15). Apparent fracture toughness (MPa.m1/2) was measured on the porcelain surface of bilayers (n=15) and residual stress was calculated. Two-way ANOVA (porcelain and cooling method) was used for the bilayer analysis (α=0.05). Vita PM9 monolayer exhibited significantly higher BFS (p<0.01), but there was no significant difference (p=0.41) in the FT between the porcelains. For bilayer specimens, the two-way ANOVA for BFS was significant for the porcelain variable only (p<0.01) better for Vita PM9/zirconia. Two-way ANOVA for the FT for the bilayers was not significant for any variable. All groups showed compressive residual stresses. The pressed porcelain seems to be mechanically more effective for zirconia veneering.
Keywords: Dental porcelain; Material resistance; Zirconium